2022
DOI: 10.3389/fmicb.2022.895844
|View full text |Cite
|
Sign up to set email alerts
|

A Satellite dsRNA Attenuates the Induction of Helper Virus-Mediated Symptoms in Aspergillus flavus

Abstract: Aspergillus flavus is an important fungal pathogen of animals and plants. Previously, we reported a novel partitivirus, Aspergillus flavus partitivirus 1 (AfPV1), infecting A. flavus. In this study, we obtained a small double-stranded (ds) RNA segment (734 bp), which is a satellite RNA of the helper virus, AfPV1. The presence of AfPV1 altered the colony morphology, decreased the number of conidiophores, created significantly larger vacuoles, and caused more sensitivity to osmotic, oxidative, and UV stresses in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 90 publications
0
7
0
Order By: Relevance
“…The functional AGOs of A. flavus needed further exploration. In a previous study, AfPV1 infection resulted in several large vacuoles in A. flavus cells ( Jiang et al, 2022 ). Here, we examined functions of sRNA affected by AfPV1 infection, and found that some GO terms and KEGG pathways are closely related to vacuole production in eukaryotic cells ( Figure 12 ), and support the previous finding that AfPV1 effects are related to vacuole formation in A. flavus cells.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The functional AGOs of A. flavus needed further exploration. In a previous study, AfPV1 infection resulted in several large vacuoles in A. flavus cells ( Jiang et al, 2022 ). Here, we examined functions of sRNA affected by AfPV1 infection, and found that some GO terms and KEGG pathways are closely related to vacuole production in eukaryotic cells ( Figure 12 ), and support the previous finding that AfPV1 effects are related to vacuole formation in A. flavus cells.…”
Section: Discussionmentioning
confidence: 79%
“…However, mycovirus-mediated hypovirulence could be used as a new type of therapy for human pathogenic fungi (Kotta-Loizou and Coutts, 2017;van de Sande and Vonk, 2019). In the previous studies, our research group found that AfPV1 is placed as a new genus in Partitiviridae family, and AfPV1-infected A. flavus showed debilitation and hypovirulence in animal and insect studies (Jiang et al, 2019(Jiang et al, , 2022. However, the interactions between the AfPV1 and A. flavus are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, satellite RNA was most recently demonstrated to attenuate the phenotypic and transcriptomic effects of Aspergillus flavus partitivirus 1 infection in A. flavus . 48 Although the detailed molecular mechanism remains unknown, suppression machinery might also have been established in mycoviruses. To further understand the relationship between fungi and viruses, the mechanisms of such co-evolutionary relationships would be a focus in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to Polymycoviridae, infection of A. fumigatus with a member of Chrysoviridae resulted in sensitivity to osmotic and oxidative stresses, but also impaired the host in the presence of formic acid and nitric oxide and under hypoxic low oxygen conditions [13]. In A. flavus, infection with a member of Partitiviridae also weakened the host against osmotic, oxidative, and ultraviolet stress [14].…”
Section: Discussionmentioning
confidence: 99%